Developing a human-environment timeline: a chronology of ideas and events for the anthropocene - Larsen, Thomas Barclay (Kansas State University, 2018)
Clearly, the character of the relationship between humans and their environment has changed over time. Scholars have developed a geologic timeline and a timeline for life, but there is not a human-environment timeline. The proposed new geologic epoch of the Anthropocene is inadequate for encapsulating the diversity of the human-environment relationship throughout history and prehistory. This dissertation initiates conversation about developing an official human-environment timeline. Oriented from the perspective of a geographer, this exploratory research involved the qualitative analysis of human-environment events and ideas from a series of four geographic encyclopedias. A human-environment timeline emerged from this research, as well as a hierarchical typology of time periods: durations, duration revolutions, scenes, scene transitions, and intervals. The timeline was then interpreted according to four “ways of knowing”: normal science, cultural ecology, political ecology, and humanistic geography. This research supports inquiry into how time periods can be employed to better understand and communicate the human-environment relationship through time.
Keywords: Anthropocene; Human-Environment; Periodization; Timeline